The Baculovirus GP64 Protein Mediates Highly Stable Infectivity of a Human Respiratory Syncytial Virus Lacking Its Homologous Transmembrane Glycoproteins - Oomens, A. G. P. (American Society for Microbiology, 2004)
Baculovirus GP64 is a low-pH-dependent membrane fusion protein required for virus entry and cell-to-cell transmission. Recently, GP64 has generated interest for practical applications in mammalian systems. Here we examined the membrane fusion function of GP64 from Autographa californica multiple nucleopolyhedrovirus (AcMNPV) expressed in mammalian cells, as well as its capacity to functionally complement a mammalian virus, human respiratory syncytial virus (HRSV). Both authentic GP64 and GP(64/F), a chimeric protein in which the GP64 cytoplasmic tail domain was replaced with the 12 C-terminal amino acids of the HRSV fusion (F) protein, induced low-pH-dependent cell-cell fusion when expressed transiently in HEp-2 (human) cells. Levels of surface expression and syncytium formation were substantially higher at 33°C than at 37°C. The open reading frames (ORFs) encoding GP64 or GP(64/F), along with two marker ORFs encoding green fluorescent protein (GFP) and β-glucuronidase (GUS), were used to replace all three homologous transmembrane glycoprotein ORFs (small hydrophobic SH, attachment G, and F) in a cDNA of HRSV. Infectious viruses were recovered that lacked the HRSV SH, G, and F proteins and expressed instead the GP64 or GP(64/F) protein and the two marker proteins GFP and GUS. The properties of these viruses, designated RSΔsh,g,f/GP64 or RSΔsh,g,f/GP(64/F), respectively, were compared to a previously described HRSV expressing GFP in place of SH but still containing the wild-type HRSV G and F proteins (RSΔsh [A. G. Oomens, A. G. Megaw, and G. W. Wertz, J. Virol., 77:3785-3798, 2003]). By immunoelectron microscopy, the GP64 and GP(64/F) proteins were shown to incorporate into HRSV-induced filaments at the cell surface. Antibody neutralization, ammonium chloride inhibition, and replication levels in cell culture showed that both GP64 proteins efficiently mediated infectivity of the respective viruses in a temperature-sensitive, low-pH-dependent manner. Furthermore, RSΔsh,g,f/GP64 and RSΔsh,g,f/GP(64/F) replicated to higher levels and had significantly higher stability of infectivity than HRSVs containing the homologous HRSV G and F proteins. Thus, GP64 and a GP64/HRSV F chimeric protein were functional and efficiently complemented an unrelated human virus in mammalian cells, producing stable, infectious virus stocks. These results demonstrate the potential of GP64 for both practical applications requiring stable pseudotypes in mammalian systems and for studies of viral glycoprotein requirements in assembly and pathogenesis.